THE CORRELATION BETWEEN STUDENTS’ LEARNING INTEREST AND THEIR ENGLISH ACHIEVEMENT AT SMAN 10 KENDARI - Yuliana, Yuliana; Sale, Firdaus; Nggawu, La Ode (Universitas Halu Oleo, 2019)
The purpose of the research is to find out a significant correlation between students' learning interest and their English achievement in SMAN 10 Kendari. The method used in conducting this research is correlation study. The results of the research show that there is significant correlation between students’ learning interest and their English achievement. It can be seen by the results of analysis using Correlation Product Moment with help program SPSS Version 16, it showed a significance value rxy is 0.382; df is 100 if it is compared with the r table at the degree of significance 5% (0.195) and 1% (0.254), the correlation between students’ learning interest and their English achievement is significant (rxy: rtable= 0.382 > 0.195; rxy: rtable = 0.382 > 0.254) it means that H0 rejected and H1 accepted. Thus it can be concluded that there was significant correlation between students’ learning interest and their English achievement at SMAN 10 Kendari in academic year 2016/2017. Keywords: Correlation, Learning Interest, English Achievement